SUCCESSFUL SURGICAL MANAGEMENT OF A COMPLEX FRONTAL LOBE AND HIPPOCAMPAL CAVERNOUS ANGIOMA: A CASE REPORT (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Cerebral cavernous angiomas (also referred to as cavernomas or cavernous malformations) are vascular abnormalities composed of clusters of dilated capillary vessels with thin walls and no intervening brain parenchyma. Although histologically benign, these lesions may have serious clinical consequences, particularly when located in functionally critical areas of the brain. Their unpredictable natural history and potential for neurological symptoms make them a subject of increasing interest in neurology and neurosurgery. Cavernous angiomas are relatively rare, occurring in approximately 0.4% to 0.9% of the general population. They may present sporadically or as part of a familial syndrome, often associated with mutations in specific CCM (Cerebral Cavernous Malformation) genes. While many lesions remain asymptomatic, a significant number become clinically relevant due to hemorrhagic events or seizure activity. The lesions typically consist of sinusoidally dilated vascular channels lined by a single layer of endothelium, often surrounded by hemosiderin deposits indicating prior microbleeds. The clinical manifestations of cavernous angiomas are highly variable and largely dependent on lesion location. Seizures are among the most common symptoms, particularly when the lesion is situated in the cerebral cortex or limbic structures such as the hippocampus. In many cases, seizures can be the initial or only presentation. Lesions may also cause progressive focal neurological deficits or acute symptoms due to hemorrhage. Patients with epilepsy related to cavernous angiomas often become resistant to pharmacologic treatment, necessitating further evaluation for surgical intervention. Magnetic resonance imaging (MRI) is the gold standard for detecting cavernous angiomas. Advanced imaging techniques, particularly susceptibility-weighted imaging (SWI) and T2*-weighted sequences, are crucial for identifying small lesions and detecting surrounding hemosiderin rings from prior bleeding. Functional imaging, including functional MRI and PET, can help assess the impact of the lesion on eloquent brain areas, while video EEG monitoring is essential in evaluating seizure focus in surgical candidates. Surgical resection is a well-established treatment option for symptomatic cavernous angiomas, especially in cases of drug-resistant epilepsy or recurrent hemorrhage. The goal of surgery is not only to remove the lesion but also to excise the surrounding gliotic and hemosiderin-stained tissue that may contribute to epileptogenesis. Advances in intraoperative neuronavigation, cortical mapping, and electrocorticography have significantly improved the safety and efficacy of surgical procedures, even in eloquent brain regions.